Control of pregnancy-associated malaria through community involvement in rural Ghana - Bam, Victoria Bubunyo (2015)
A Thesis submitted to the Department of Community Health, Kwame Nkrumah University of Science and Technology in Partial fulfillment of the requirement for the degree of Doctor of Philosophy (Community Health)School of Medical Sciences, College of Health Science. DBL-Centre of Health Research and Development, University of Copenhagen, Denmark,